THU0459-HPR Anxiety and depression scores reduction after six-months of biology therapy. (23rd January 2014) - Marques, A.A.; Ferreira, R.; Santiago, T.
Abstract : Background: Depression and anxiety are common in patients with rheumatic diseases and are associated with diminished health status and increased health care utilization. Objectives: To evaluate the effect of biologic therapy regarding anxiety and depression scores in patients followed in the Day-Hospital of Rheumatology Department after 6-months.To explore the correlation of these two Mental Health scores with demographic and clinical variables. Methods: Consecutive biologic treated patients beginning biological therapy were included. The Portuguese validated version of Hospital Anxiety and Depression Scale (HADS) was assessed using the self-questionnaire. Patients were characterized for demographic characteristics, functional capacity (HAQ), disease activity (DAS283vorBASDAI) and Pain and Disease Activity Visual Analogical scale at baseline, 3 months and 6 months. As primary outcome anxiety and depression reduction were evaluated with Wilcoxon Signed Ranks Test. For second outcome analyses Spearman Correlation Coefficient was performed. We considered p<.05 for statistically significant differences using SPSS Ò 17.0 version. Results: Since January 2011 seventeen patients were included (12 females, mean age 48.23±14.2 years), diagnosed with rheumatoid arthritis (7), psoriatic arthritis (5), spondylitis anquilosant (3) and idiopatic juvenile arthritis (2), and medicated with etanercept (9), tocilizumab (3); infliximab (3) and adalimumab (2). From baseline to 6-months this patients improved on: Disease Activity Perception (n=17 = 67.2±14.0 to n=17 = 28.1±20.7) pain (n=17 = 61.1±11.2 to n=17 = 26.2±18.2), HAQ (n=12 = 1.5±0.4 to n=12 = 0.6±0.4), DAS28 3v (n=11 = 4.66±1.18 to n=11 = 2.60±0.88), BASDAI (n=5 = 6.77±1.26 to n=5 = 1.89±1.26). After 3-months we observed a statistically significant reduction on Anxiety (Z=-3.531, p=.000;14 patients decrease and 3 increase) and Depression (Z= -3.107, p=0.002;13 decrease and 4 increase). Similar but better results were observed at 6-months on Anxiety (Z= -3.287, p=0.001; 16 decrease and 1 increase)and Depression (Z= -2.542, p=.011; 14 decrease, 2 increase and 1 tie). The variation of Anxiety and Depression at 6 months does not have statistically significant correlation with any of other variables variation (p>0.05) witch not allowed us to perform a multiple linear regression analysis. Conclusions: Biologic therapy conducted to a high reduction on Anxiety and Depression scores even after 3 months, with better results as 6-months. The non correlation with other variables variation leads us to conclude that probably this mental health conditions deserve a particular attention on clinical practice and further research. To face the limitations of this study we want to improve the sample and to evaluate Anxiety and Depression with other instruments (SF-36, psychiatric evaluation). Disclosure of Interest: None Declared